2018
DOI: 10.5194/tc-12-3635-2018
|View full text |Cite
|
Sign up to set email alerts
|

Marine ice sheet instability and ice shelf buttressing of the Minch Ice Stream, northwest Scotland

Abstract: Abstract. Uncertainties in future sea level projections are dominated by our limited understanding of the dynamical processes that control instabilities of marine ice sheets. The last deglaciation of the British–Irish Ice Sheet offers a valuable example to examine these processes. The Minch Ice Stream, which drained a large proportion of ice from the northwest sector of the British–Irish Ice Sheet during the last deglaciation, is constrained with abundant empirical data which can be used to inform, validate, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 70 publications
(106 reference statements)
4
39
0
Order By: Relevance
“…BISICLES was chosen for its efficient and accurate representation of the dynamics of marine grounded ice sheets and for its process‐representation permitting ice shelf formation, grounding line migration, and ice surface lowering. BISICLES has previously been applied to simulations of both contemporary (e. g., Antarctica , Cornford et al, 2015; Berger et al, 2016) and paleo ice sheets (e.g., The British‐Irish Ice Sheet; Gandy et al, 2018, 2019), as well as to smaller icefields (e.g., Patagonia). The dynamical equations in BISICLES fall into type “L1L2” of hybrid ice sheet modeling approaches (Hindmarsh, 2004), where the longitudinal stresses are treated as depth dependent, and are included in the computation of stresses driving the ice flow (Schoof & Hindmarsh, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…BISICLES was chosen for its efficient and accurate representation of the dynamics of marine grounded ice sheets and for its process‐representation permitting ice shelf formation, grounding line migration, and ice surface lowering. BISICLES has previously been applied to simulations of both contemporary (e. g., Antarctica , Cornford et al, 2015; Berger et al, 2016) and paleo ice sheets (e.g., The British‐Irish Ice Sheet; Gandy et al, 2018, 2019), as well as to smaller icefields (e.g., Patagonia). The dynamical equations in BISICLES fall into type “L1L2” of hybrid ice sheet modeling approaches (Hindmarsh, 2004), where the longitudinal stresses are treated as depth dependent, and are included in the computation of stresses driving the ice flow (Schoof & Hindmarsh, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…The conditions at the ice-bed interface (melting or non-melting), the availability of liquid water and mechanical properties of the till (soft or hard) thus control the processes that can be activated. A simple hydrology scheme has recently been added to BISICLES to allow for the self-generation of ice streams by representing basal sliding with a Coulomb law sensitive to the presence of till water (Gandy et al, 2019). However, this scheme is not included in the version of BISICLES used here.…”
Section: Basal Processesmentioning
confidence: 99%
“…Recently, a simple basal sliding scheme has been added into BISICLES. The scheme uses a Coulomb sliding law sensitive to the presence of till water and is able to simulate well the ice streams of the British-Irish Ice Sheet (Gandy et al, 2019). However, the version of BISICLES we used here does not yet include these processes of basal hydrology that are needed to generate ice streams.…”
Section: Basal Tractionmentioning
confidence: 99%
“…equilibrium simulations) run at 1-ka intervals for 26-21 ka and 500-year intervals for 21-0 ka. They are the same simulations used and described in more detail by Morris et al (2018), Swindles et al (2018) and Gandy et al (2018). The snapshots represent a refinement from earlier HadCM3 simulations (Singarayer et al, 2011;Singarayer and Valdes, 2010), and have been updated according to boundary conditions provided for the Palaeoclimate Model Intercomparison Project Phase 4 protocol for simulations of the last deglaciation (version 1; Ivanovic et al, 2016), using the ICE-6G_c reconstruction (Peltier et al, 2015).…”
Section: Surface Mass Balance and Climate Inputsmentioning
confidence: 99%
“…They showed that the movement of the grounding line, overall mass loss and evolution of fast-flowing ice streams are all sensitive to increasing the mesh resolution and features in bed geometry (Cornford et al, 2015;Lee et al, 2015). A recent study applied BISICLES in a palaeo setting, focussing on simulating part of the British and Irish ice sheet, and highlighted the importance of marine interactions and marine ice sheet instability during the last deglaciation of the British Isles (Gandy et al, 2018). https://doi.org/10.5194/gmd-2019-304 Preprint.…”
Section: Introductionmentioning
confidence: 99%